Morphogenesis of pericellular liver fibrosis in patients with chronic viral hepatitis C associated with hepatic steatosis - V. A. Tumanskiy; Yu. A. Shebeko; E. A. Gromenko; S. V. Fen' (Zaporozhye State Medical University, 2012)
The research of pathomorphological features of liver fibrosis in patients with chronic viral hepatitis C associated with hepatic steatosis has shown that as opposed to cases of perisinusoidal-central-lobular and portal-septal fibrosis, typical for chronic viral hepatitis C without steatosis, in patients with chronic viral hepatitis C with steatosis in areas of maximal hepatocyte steatosis and steatic cysts firstly focal pericellular-lobular fibrosis develops which then progresses into pericellular intralobular severe liver fibrosis.